KEPEMIMPINAN TRANSFORMASIONAL: IGNASIUS JONAN - Hermina S; Jerry Indrawan (PARAPOLITIKA: Journal of Politics and Democracy Studies, 2020)
This paper is to analyze transformational leadership organized by Ignatius Jonan. This study found facts Ignatius Jonan is a leader with transformational leadership. Ignatius Jonan has succeeded in bringing change for the better eg, the face of KAI's better service, finally success the transformation process into believe in the Working Cabinet.